2020
DOI: 10.1136/bmjopen-2019-036349
|View full text |Cite
|
Sign up to set email alerts
|

Methodological quality of meta-analyses indexed in PsycINFO: leads for enhancements: a meta-epidemiological study

Abstract: ObjectivesMeta-analyses (MAs) are often used because they are lauded to provide robust evidence that synthesises information from multiple studies. However, the validity of MA conclusions relies on the procedural rigour applied by the authors. Therefore, this meta-research study aims to characterise the methodological quality and meta-analytic practices of MAs indexed in PsycINFO.DesignA meta-epidemiological study.ParticipantsWe evaluated a random sample of 206 MAs indexed in the PsycINFO database in 2016.Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…16 It is disappointing that the overall confidence in most SRs of interventions for mental and behavioural disorders is low to critically low as already shown in various clinical fields. 4,5,8,[11][12][13][14][15] While authors of SRs are primarily responsible for the quality of their work, the 'gatekeepers' of scientific publishing (peer-reviewers and journal editors) are equally responsible for guiding SR authors through the publication process, especially if the authors are new in the field of research synthesis or are not English speakers.…”
Section: Application Of Amstar2mentioning
confidence: 99%
See 2 more Smart Citations
“…16 It is disappointing that the overall confidence in most SRs of interventions for mental and behavioural disorders is low to critically low as already shown in various clinical fields. 4,5,8,[11][12][13][14][15] While authors of SRs are primarily responsible for the quality of their work, the 'gatekeepers' of scientific publishing (peer-reviewers and journal editors) are equally responsible for guiding SR authors through the publication process, especially if the authors are new in the field of research synthesis or are not English speakers.…”
Section: Application Of Amstar2mentioning
confidence: 99%
“…SRs are typically appraised to identify common problems, including methodological limitations and/or poor reporting. 3,4,[13][14][15][20][21][22][23][24][25] While the focus of AMSTAR2 is on the methodological quality, this tool is highly sensitive to poor reporting. Specifically, inadequate reporting of only 2/16 items can be sufficient to assign a critically low confidence rating to a SR.…”
Section: Suggestions For Using Amstar2mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that several previous studies reported insufficient assessment of RoB of primary studies included in SR/MAs [ 21 , 28 , 29 , 30 , 31 ], we did not identify any studies that would formally test such a variable as a predictor of SR quality. However, previous studies showed that involvement of a ‘research methodologist’ predicts a higher quality of SRs.…”
Section: Discussionmentioning
confidence: 90%
“…Most studies report similar results, with a large number of SRs included being rated as low or critical low quality. (23)(24)(25)(26)(27) Currently, there are some quality appraisal tools and guidelines that might help authors and peer reviewers to improve and assess methodological report and review of SRs. The AMSTAR II is one of these tools.…”
Section: Discussionmentioning
confidence: 99%